Restorative effects of Lactobacillus rhamnosus LR-32 on the gut microbiota, barrier integrity, and 5-HT metabolism in reducing feather-pecking behavior in laying hens with antibiotic-induced dysbiosis - Huang, Chenxuan; Yue, Qiaoxian; Sun, Li; Di, Keqian; Yang, Duanli; Hao, Erying; Wang, Dehe; Chen, Yifan; Shi, Lei; Zhou, Rongyan; Zhao, Guoxian; Chen, Hui (Frontiers in Microbiology, 2023)
The development of abnormal feather-pecking (FP) behavior, where laying hens display harmful pecks in conspecifics, is multifactorial and has been linked to the microbiota-gut-brain axis. Although emerging studies have demonstrated the role of gut microbiota in modulating FP behavior, the mechanism(s) underlying these processes remain unclear. In the present study, dietary supplementation with the antibiotic, lincomycin hydrochloride, was utilized to induce intestinal dysbacteriosis in laying hens. Antibiotic exposure reduced egg production performance and increased the tendency for severe feather-pecking (SFP) behavior in laying hens, accompanied by damages to intestinal barrier and blood-brain barrier function, and inhibition of 5-HT metabolism. However, treatment with Lactobacillus rhamnosus LR-32 following antibiotic exposure significantly alleviated the decline in production performance and reduced SFP behavior. Lactobacillus rhamnosus LR-32 supplementation restored the profile of the gut microbial community, and showed a strong positive effect by increasing expression of tight junction proteins in the ileum and hypothalamus and promoting the expression of genes related to central 5-HT metabolism. Overall, our findings indicate that dietary supplementation with Lactobacillus rhamnosus LR-32 can reduce antibiotic-induced FP in laying hens and is a promising treatment to improve the welfare of domestic birds.